Wahnanalysen - Stompe, Thomas; Stompe, Thomas (Berlin MWV Medizinisch Wissenschaftliche Verlagsgesellschaft, 2012)
The discussion of the meaning and meaning of delusional reports has come to the fore again in recent years - despite the undoubted success of psychopharmacology treatment since the introduction of antipsychotics. This book is devoted to analyzing the meaning of delusion as the most fascinating and enigmatic phenomenon in psychopathology and examines it from the perspective of different therapy schools. Descriptive psychopathologists, systems theorists, Freudian, Kleinian and Lacanian provenance psychoanalysts, C.G. Jung, existential analyst and content analyst. The articles deal with the concepts of the respective therapy schools, the examination methods and mindsets on the subject of delusion. This is followed by the analysis of two delusions. With this unique approach to the phenomenon of delusion, the book enriches everyone involved in the treatment of psychotic illnesses and provides a comprehensive overview of how to deal with delusional patients.
German
Keywords: Psychiatry; delusion; psychopathology; psychosis